Peranan Zona Pelusida Sebagai Barier Terhadap Cemaran Escherichia coli K99 (THE ROLE OF ZONA PELLUCIADA AS A BARRIER OF E COLI K99 CONTAMINATION) - Batan, I Wayan; Lay, Bibiana Widiati; Djuwita, Ita; ., Supar; Boediono, Arief (Jurnal Veteriner, 2013)
The aim of the study was to investigate the role of zona pelucida (ZP) as a barrier of embryo againstE.coli K99 contamination.   The complete randomized design was used in this study.  The embryos weregiven treatment as a follow : 1) embryos without ZP were contaminated with E.coli K99;  2) embryo withintact ZP were contaminated with E.coli K99;  and  3) embryos  with intact ZP were not contaminated withE.coli K99, as a control.  In each treatment there was 15 replication and in each replication there was oneembryo.  The embryos were incubated in incubator at 37°C and 5% CO2 atmosphere.  The embryos wereobserved every six hours in 24 hours using inverted microscope.  The result showed that embryos withintact ZP could develop in culture contaminated with  E.coli K99, while embryos without ZP becomedegenerated.  The viability of intact embryos was 75% and the embryos without ZP were 65%.  Embryosculture in contaminated medium could develop from eight cells embryo into morulla stage of embryo,compact morulla, and blastocyst. E.coli K99 contamination could inhibit embryo development.  In conclusion,ZP could protect embryo against E.coli K99 contamination.
Keywords: embryo, zona pelucida, E.coli K99